The Role of BCL-2 and BAK Genes in Chronic Kidney Disease and Haemodialysis Patients - Hanan Nour; Nariman Zahran; Samah Abd Elhamid; Manal Zahran; Manar Raafat; Asmaa El Saeed (Journal of Glycomics And Metabolism, 2016)
Background: Polymorphonuclear leucocytes are the first line of defence against foreign invaders and constitute the major cell type involved in certain types of acute and chronic inflammatory diseases. Aim of the Work: The aim of the present study was to investigate the changes in expression of BCL-2 and BAK genes by real time PCR and to study whether they were involved in the accelerated neutrophil apoptosis which might be responsible for the recurrent bacterial infections seen in chronic renal disease and hemodialysis patients. Subjects and Methods: This study was conducted on sixty two subjects. Patients were selected from those admitted to Theodor Bilharz Research Institute (TBRI). Patients under study were classified into three groups; CKD patients (group I) kept on conservative treatment (22 cases), ESRD patients (group II) maintained on dialysis therapy, HD (20 cases). In addition, twenty healthy individuals served as a control group (group III) were involved. Results: There was significant increase in level of BAK gene in both patients' groups compared to control group with more increase in CKD group than ESRD group. Significant difference between the 3 groups was encountered with a higher expression level in CKD and ESRD groups than controls. There was decrease in level of BCL2 gene in both groups less than control group with more declines in ESRD group than CKD group. Conclusion: Bcl2 and Bak genes could have a role in survival and apoptosis of the studied groups and suggested their impact in controlling the inflammatory mechanisms and eventually their therapeutic potential.
Keywords: RQ-PCR